Juridical Review of Hazardous and Toxic Waste Management - Gustika Sandra; Tarmizi Tarmizi; Dewi Mulfiyanti (Borong Newinera Publisher, 2023)
This research aims to determine the juridical review of the management of hazardous and toxic waste (LB3) at Tenriawaru Hospital, Bone Regency. This research is field research conducted at Tenriawaru Hospital, Bone Regency using qualitative data collection and analysis methods. The data sources in this research are primary data, namely data obtained from interviews with informants and secondary data in the form of statutory regulations. The research results show that the management of hazardous and toxic waste at Tenriawaru Bone Regional Hospital is carried out by sorting, storing, transporting and burying. Management of B3 waste at Tenriawaru Bone Hospital is in accordance with the Minister of Environment Regulation Number 18 of 2009 concerning Procedures for Licensing Management of Hazardous and Toxic Waste Article 2 paragraph (1), namely the type of B3 waste management activity that must be accompanied by a permit consists of transportation activities, temporary storage, collection, utilization, processing and stockpiling. Regarding the use of medical waste, it is not mandatory considering that medical waste is very dangerous and can cause disease and is dangerous to health. Management has been carried out in a structured manner, but still needs to be strengthened in terms of control so as not to pollute the environment. To prevent the negative impact of the management of hazardous and toxic waste (LB3), especially medical waste in hospitals.